Preoperative Biometry and Uncorrected Visual Outcome Following Cataract Surgery at a Teaching Hospital at Western Part of Nepal - Thapa, Bikram Bahadur; Adhikari, Basu Prasad; Gurung, Nanda Kumari; Verma, Jitendra Kumar (Journal of Nepalgunj Medical College, 2022)
Introduction: Proper preoperative biometry in cataract surgery provides expected postoperative uncorrected visual outcome. Astigmatism is one of the major problems to achieve best postoperative unaided visual acuity. Aims: To determine the distribution of biometric parameter and unaided visual outcome in the cataract patients operated at Nepalgunj medical college, Banke, Nepal. Methods: The patients who underwent cataract surgery between January 2019 and December 2020 at Nepalgunj medical college were studied. Patient’s demographic parameter, keratometric value, anterior chamber depth, lens thickness and axial length data, type of surgery, preoperative and post-operative visual acuity and other clinical details were collected and analyzed. Results: This study enrolled 261 eyes of 261 patients who had undergone cataract surgery. The mean age of patients was 60.8 ± 14.62 years. The mean corneal astigmatism was 1.30±1.43 D. Corneal astigmatism was higher than 1.00 D in almost 40% of cases. With-therule astigmatism was the most common type (46.4%) of astigmatism observed in this study. The mean average keratometry was 44.83±2.05 D. The mean preoperative LogMAR VA of 1.52±0.83 improved to 0.48 ± 0.48 postoperatively without statistically significant differences between manual small incision cataract surgery and phacoemulsification technique (p=0.496). Conclusion: The biometric data helps to improve surgical procedure and select most appropriate intraocular lens to attain maximal postoperative uncorrected visual acuity following cataract surgery. This study found superior convention incision is better for cataract surgery with equivalent visual outcome following manual small incision cataract surgery and phacoemulsification.